Single-cell analysis reveals that stochasticity and paracrine signaling control interferon-alpha production by plasmacytoid dendritic cells - Florian Wimmers (Nature Portfolio, 2018)
Plasmacytoid dendritic cells (pDC) are a pivotal component of the immune system. Here, the authors utilize single-cell microfluidics to interrogate the human pDC compartment and reveal a subset of type I IFN secreting pDCs that is regulated by stochastic gene expression and amplified by microenvironmental cues.